Variations in Reactive Oxygen Species Generation by Urban Airborne Particulate Matter in Lung Epithelial Cells—Impact of Inorganic Fraction - Mazuryk, Olga; Stochel, Grazyna; Brindell, Małgorzata (Frontiers in Chemistry, 2020)
Air pollution is associated with numerous negative effects on human health. The toxicity of organic components of air pollution is well recognized, while the impact of their inorganic counterparts in the overall toxicity is still a matter of various discussions. The influence of airborne particulate matter (PM) and their inorganic components on biological function of human alveolar-like epithelial cells (A549) was investigated in vitro. A novel treatment protocol based on covering culture plates with PM allowed increasing the studied pollutants concentrations and prolonging their incubation time without cell exposure on physical suffocation and mechanical disturbance. PM decreased viability of A549 cells, disrupted their mitochondrial membrane potential and calcium homeostasis. For the first time the difference in the reactive oxygen species (ROS) profiles generated by organic and inorganic counterparts of PM was shown. Singlet oxygen generation was observed only after treatment of cells with inorganic fraction of PM, while hydrogen peroxide, hydroxyl radical and superoxide anion radical were induced after exposure of A549 cells to both PM and their inorganic fraction.